A statistical evaluation of water quality trends in selected water bodies of Newfoundland and Labrador. Issue 1 (1st January 2006) - Dawe, Paula
Abstract : Using water quality data collected since 1986, as part of the Canada–Newfoundland Water Quality Monitoring Agreement, 36 different water quality variables from 65 different water quality monitoring sites were examined for change over time. Moving averages, the Student's t test statistic, and Spearman's rank correlation coefficient were used. Throughout the province, turbidity and colour were generally displaying deteriorating trends, while conductivity, copper, lead, and mercury were consistently displaying improving trends. There was a notable deteriorating trend in nitrate and nitrite and nitrogen in select river basins, and an improving trend in phosphorous in more developed basins. Even in pristine watersheds, change was often observed in metals, major ions, turbidity, and colour. An examination of land and water use activities ongoing in each watershed allowed identification of likely localized causes and (or) factors contributing to observed water quality trends. In many cases trend-causing factors appeared to be more global in nature and most trends could be explained by an upward trend in river flows during the period analyzed. Key words : water quality, Newfoundland, Labrador, trends, Spearman, land use, statistics, streamflow.